The Effect of Authentic Material towards Students Tenses Mastery - Maximilian, Aksendro (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The objective of this research was to know the influence of using authentic material towards students` tenses mastery. This research was conducted at SMP Muhammadiyah 1 Way Sulan 1 Lampung Selatan in 2015/2016. The writer conducted this research by using quasi-experimental method. The sample of this research were 2 classes, they were VIIIA as the experimental class and VIIIB as the control class. The writer used cluster random sampling technique in taking the sample. For the data collecting technique, the writer used tenses test. This research showed that there was a significant influence of authentic material towards studentsâ tenses mastery at the eighth class of SMP Muhammadiyah 1 Way Sulan Lampung Selatan 2015/2016. It was proved by the result of ttest was higher than ttable with significance level 5% and 1% (1.67<2.51>2.39). It can be concluded that the authentic material has positive significant influence in improving studentsâ tenses mastery.